Determinants of Original Local Government Revenue In North Sumatera Province - Bella Sapira; Shita Tiara; Rizqy Fadhlina Putri (Westscience Press, 2023)
The amount of Original Local Government Revenue has increased and decreased every year, in 2020 where the economy in Indonesia was heavily affected by the Covid-19 Pandemic, Original Local Government Revenue has decreased by 6 percent from 2019. The objective of the research was to determine the effect of GRDP, total population, number of labor forces, regional taxes, results of management of separated regional assets, and other legal Original Local Government Revenue toward Original Local Government Revenue of North Sumatra Province. North Sumatera Province is the population in this research. The sample selection method was to use a saturated sampling technique. Secondary data was to use panel data consisting of 2019 to 2021. Data analysis was to use multiple linear regression analysis. The results of the research stated that partially GRDP had a significant effect on Original Local Government Revenue, partially Population had a significant effect on Original Local Government Revenue, partially the number of workforce had no effect on Original Local Government Revenue, partially Regional Tax had a significant effect on Original Local Government Revenue, partially the results of management of separated regional assets did not affected Original Local Government Revenue, partially other Legal Original Local Government Revenue did not affect Original Local Government Revenue. Simultaneously the variables of GRDP, total population, number of labor force, regional taxes, results of management of separated regional assets, other legal Original Local Government Revenue affected Original Local Government Revenue. It is hoped that the government could explore more other sources of Original Local Government Revenue to support sources of financing from the region itself.